Definition of Doriclytus, stat. rev. as a subgenus of Polynema and redescription of its type species, P. (Doriclytus) vitripenne (Hymenoptera: Mymaridae) - Triapitsyn, Serguei V.; Fidalgo, Patricio (Zootaxa, 2006)
Doriclytus Foerster is redescribed and treated as a subgenus of the common, diverse, and widespread genus Polynema Haliday (Mymaridae). Its type species, P. (Doriclytus) vitripenne (Foerster), is redescribed based on the holotype as well as more recently collected specimens from Russia, Sweden, and Belgium. The Neotropical genera Restisoma Yoshimoto and Formicomymar Yoshimoto, both syn. n., are synonymized under Polynema (Doriclytus) and their type species are transferred to Polynema as, respectively, P. (Doriclytus) howdeni (Yoshimoto) and P. (Doriclytus) venezuelaense (Yoshimoto), both comb. n. Barypolynema Ogloblin, syn. n. and Notopolynema Ogloblin, syn. n. are synonymized under P. (Doriclytus); Tarphypolynema Ogloblin, syn. n., described originally as a subgenus of Barypolynema, is synonymized under the nominate subgenus Polynema (Polynema). A key to the three presently recognized subgenera of Polynema s. l. is provided.